Annotated Checklist of the large branchiopod crustaceans of Idaho, Oregon and Washington, USA, with the “rediscovery” of a new species of Branchinecta (Anostraca: Branchinectidae) - Rogers, D. Christopher; Hill, Matthew A. (Zootaxa, 2013)
We present a checklist of the large branchiopod crustaceans of Idaho, Oregon and Washington, USA. New distributional records are presented for most species, including the first records of Branchinecta constricta Rogers, 2006 and Lepidurus cryptus Rogers, 2001 from Idaho, the first record of B. oriena Belk & Rogers 2002 from Oregon, the first record of B. mackini Dexter, 1956 and Artemia franciscana Kellogg, 1906 co-occurring, and the first record of L. cryptus from Washington. Furthermore, we present the first record of Eulimnadia diversa Mattox, 1937 from west of the continental divide, which we interpret as an accidental introduction. In 1959, Lynch collected a new fairy shrimp species from Washington, deposited that material in the US National Museum, labeled “muddy fairy shrimp, Branchinecta lutulenta”, but never described it. Numerous efforts have been made to rediscover extant populations since 1999. We rediscovered this species in 2011, from two small pools from the vicinity of Lynch’s original collection site, which appears to have been destroyed. Branchinecta lutulenta sp. nov. is most closely related to B. lindahli Packard, 1883 and B. oterosanvicentei Obregón-Barboza et al., 2002. Branchinecta lutulenta sp. nov. is readily separable from all other Branchinecta species by the form of the male second antennal distal antennomere and the ornamentation of the female dorsum.